MicroRNA-3935 promotes human trophoblast cell epithelial-mesenchymal transition through tumor necrosis factor receptor-associated factor 6/regulator of G protein signaling 2 axis - Meiyuan Jin; Shouying Xu; Jiayong Li; Yingyu Yao; Chao Tang (BMC, 2021)
Abstract Background Insufficient migration and invasion during trophoblast epithelial-mesenchymal transition (EMT) results in the occurrence and development of preeclampsia (PE), and our previous study has screened 52 miRNAs, whose expression levels are altered in the placental samples from PE patients, compared with the normal group. Among those, miR-3935 is one of the miRNAs being most significantly down-regulated, indicating its involvement in PE. However, the exact effect and molecular mechanisms remain unknown. Methods In the present study, we investigate the roles and underlying mechanisms of miR-3935 in trophoblast EMT by use of the human extra-villous trophoblast cell line HTR-8/SVneo as well as human placental tissues and maternal blood samples obtained from 15 women with normal pregnancies and 15 women with PE. Experimental methods include transfection, quantitative reverse transcription-PCR (qRT-PCR), western blot, immunofluorescence staining, dual-luciferase assays, in vitro invasion and migration assays, RNA-Seq analysis, bisulfite sequencing and immunohistochemistry staining. Results MiR-3935 expression is significantly decreased in both placentas and peripheral blood specimens of PE, and functionally, miR-3935 promotes EMT of trophoblast cells. Mechanistically, TRAF6 is identified to be a direct target of miR-3935 and TRAF6 exerts its negative effect on EMT of trophoblast cells by inhibition of RGS2, which down-regulates the methylation status of promoter of CDH1 gene that encodes E-Cadherin protein through induction of ALKBH1, resulting in increase of E-Cadherin and subsequently insufficient trophoblast EMT. Conclusions Together these results uncover a hitherto uncharacterized role of miR-3935/TRAF6/RGS2 axis in the function of human trophoblasts, which may pinpoint the molecular pathogenesis of PE and may be a prognostic biomarker and therapeutic target for such obstetrical diseases as PE.